A rare case report on 90 day glaucoma due to branched retinal vein occlusion - Kuli, Jawahar Jyoti; Rai, Utkarsh (International Journal of Research in Medical Sciences, 2021)
A 19 year old female, presented to the ophthalmology OPD with pain and redness in her left eye since 30 days. Upon examination, there was no perception of light in left eye, both the pupils were mid-dilated and non-reactive to light stimulation. The left eye intra-ocular pressure (ATn) was 60 mm of Hg. On slit lamp examination, 3600 iris neovascularisation, ciliary congestion and corneal oedema were noted. Indirect gonioscopy revealed grade I angle closure in the left eye. Fundus examination of the affected eye revealed pale optic disc, CDR of 0.9:1, multiple dot and blot hemorrhages, suggestive of supero-temporal BRVO (branched retinal vein occlusion). Fundus fluorescein angiography revealed blocked fluorescence and leakage from neovascularization in the left eye. Conservative management with anti-glaucoma drugs failed to lower the IOP. Subsequently, pan-retinal photocoagulation (PRP) with intravitreal anti-VEGF (vascular endothelial growth factor) in the left eye followed by cyclo-cryoablation helped her symptoms to subside.